Evaluation of two alternative methods for disinfection of toothbrushes and tongue scrapers - Spolidório, Denise Madalena Palomari [UNESP]; Tardivo, T. A. [UNESP]; dos Reis Derceli, J. [UNESP]; Neppelenbroek, K. H.; Duque, C.; Spolidório, Luis Carlos [UNESP]; Pires, J. R. (Wiley-Blackwell, 2011)
Objective: The aim of this study was to investigate the effectiveness of two alternatives methods for the disinfection of oral cleaning devices. Methods: One type of toothbrush and two types of tongue scrapers (steel and plastic) were tested in this study. Sixteen specimens of each group were cut with standardized dimensions, contaminated separately with Candida albicans, Streptococcus mutans and Staphylococcus aureus and incubated for 24 h. After this, oral cleaning devices were washed in saline solution to remove non-adhered cells and divided into two groups (n = 8), one irradiated in microwave and other immersed in 3.78% sodium perborate solution, and evaluated for microbial recovery. The values of cfu of each group of microorganism after disinfection were compared by Kruskal-Wallis and Dunn non-parametric test, considering 95% of confidence. Results: The toothbrush harboured a significant larger number of viable organisms than the tongue scrapers. The steel tongue scraper was less susceptible to adhesion of the three oral microorganisms. The time required to inactivate all contaminating microorganisms using microwave oven was 1 min and, for the immersion in 3.78% sodium perborate solution, was 2 and 3 h, respectively, for C. albicans and S. mutans/S. aureus. Conclusion: Microwave irradiation proved to be an effective alternative method to the disinfection of tongue cleaners and toothbrushes.
Keywords: disinfection; microwaves; sodium perborate; tongue scrapers; toothbrushes